Placement test for the curriculum "Al-'Arabeiatu Baina Yadayka" - Student's Book II - Analytical Study - Elsharkawy, Moustafa Abdelkader Hafez Fathalla (Journal of Curriculum and Teaching Methodology, 2022)
Testing is a tool for measuring the levels of knowledge of individuals, it is a tool of assessing and evaluating the curricula of learners and learners. Therefore, those interested in education are keen to find and develop this important tool at all times. The Arabic Curriculum for Teaching Arabic for Non-Native Speakers (the first version) is one of the most advanced curricula used in some private schools in Pattani, southern Thailand. The Curriculum is divided into three levels (Beginner, intermediate and advanced). The student studies three books in the same order. The second is a test to determine the student's competence and readiness to begin the study of the intermediate level. This test is the field of this study, which the researcher deals with in description and analysis, to find its specifications in terms of honesty and objectivity and his ability to measure various levels of language skills. The researcher reached the following results: The test was characterized by focusing on the lower cognitive levels (memory and perception), and this may be appropriate to the objective for which it is. The test was objective; its questions were specific and short answers, with less effects of self-corrected and personality. The test is relatively honest; it provides a measure of what It put for; reading and writing skills, and I say relatively well, because the authors also set a topic for measuring the level of the student who wants to study the second level, which includes four skills, not just two skills. The test was characterized by the practically; it was placed in the front of the second book in a hundred questions varied between right and wrong questions, multiple choice, complete, match, and arrange.
Keywords: Test; Analytical Study; Determination Level; Arabic; Arabic Analysis